The MANAJEMEN STRATEGIS PROGRAM UNGGULAN; ASAH BAKAT, KECAKAPAN HIDUP DAN RISET UNTUK MEWUJUDKAN SEKOLAH BERMUTU - Rejeki, Sari; Azainil, Azainil; Hidayanto, Dwi Nugroho (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2024)
The current disruption era, schools are required to have flagship programs to improve quality. This research describes: 1) planning, 2) implementation, 3) evaluation, 4) reasons for consumer satisfaction with super talent, life skills and research programs. Case study type qualitative research. Data collection techniques use interviews, observation and document study. Informants were principals, deputy principals, teachers, parents and students. Data analysis uses the Milles and Huberman model for collecting, reducing, presenting data and drawing conclusions. Test the validity of the data using triangulation of sources and techniques. The results of the research are: 1) planning begins with environmental analysis, formulation of vision and superior programs, 2) organization and implementation super talent, life skills and research; 3) evaluation consists of program evaluation and follow-up. 4) Consumers are satisfied with the superior program, because it improves school quality. This research can be a reference for similar schools to develop quality schools.